The Mediating Role of Time Attitude and Time Metaphorical Perception in the Relationship between Mindfulness and Procrastination - Fatteme Raiisi; Sedighe Khanifar; Reza Mohamaddoust (مطالعات روانشناختی)
This study was conducted to investigate the mediating role of time attitude and time metaphorical perception in the relationship between mindfulness and procrastination. The method of this descriptive-correlation study was based on structural equation modeling. The statistical population of the research included all the students of the Islamic Azad University- Karaj branch in 2023, from which 300 students were selected through available sampling. The participants completed the Procrastination, Mindfulness, Time Attitude Scales, and Time Metaphorical Perception Questionnaire. Data were analyzed using Pearson correlation and structural equations modeling. The results showed that procrastination had negative and significant relationship with mindfulness. The effect of  positive time attitude and time metaphorical perception on mindfulness was positive and directly meaningful and the effect of  negative time attitude on mindfulness was negatively significant. Furthermore, time attitude and time metaphorical perception played mediating role in the relationship between procrastination and students' mindfulness. On the other hand, the procrastination had a negative and significant relationship with mindfulness through the mediation of negative time attitudes. Therefore, it is suggested that behavioral sciences researchers should pay attention to factors related to time from different dimensions to study the foundation of students' procrastination.